AN INVESTIGATION OF THE THERMODYNAMICS AND KINETICS EFFECT OF AMINO ACIDS ON GAS HYDRATE FORMATION - BORECHO BAVOH, CORNELIUS (2017)
Gas hydrate form and plug oil and gas pipelines, hence, they are unwanted and must be avoided. Conventionally used inhibitors are environmentally unfriendly, volatile, expensive and/or ineffective. Amino acids (AAs) are recently introduced as hydrate inhibitors. However, more thermodynamics and kinetics gas hydrate data for AAs is needed for developing effect AAs based hydrate inhibitors. This work reports an experimental study of the thermodynamic and kinetic inhibition effect of five AAs (glycine, alanine, proline, serine and arginine) on CH4 and CO2 hydrate formation in a sapphire hydrate cell reactor. The thermodynamic inhibition impact of AAs was evaluated by measuring the hydrate-liquid-vapour-equilibrium (HLwVE) curve in a pressure range of 2.53 – 9.98 MPa, and concentration range of 5 – 20 wt%, by employing the isochoric T-cycle method. The kinetic inhibition effect was studied by determining the induction time, apparent rate constant and total gas uptake during CH4 and CO2 hydrate formation from 0.5 – 2 wt% at 7.1 MPa and 3.6 MPa respectively, and 274.15 K. Prior to the experimentation, all AAs were screened as potential gas hydrate inhibitors via their sigma profile and hydrogen bonding energies predictions using COSMO-RS. The results revealed that, all studied AAs inhibited CH4 and CO2 hydrate formation via hydrogen bonding interactions with water. Glycine showed the highest inhibition impact with an average depression temperature for CH4 and CO2 hydrate of 1.78 K and 1.83 K at 10 wt%, respectively. In addition, the predicted HLwVE in AAs agreed with the experimental data. The studied AAs inhibited CH4 and CO2 hydrates formation. Glycine was found to show the best kinetic inhibition effect. Glycine significantly reduced the CH4 hydrate initial rate and uptake than PVP above 1 wt%. The hydrate nucleation/growth inhibition mechanism was found to be achieved via local water perturbation and gas dissolution reduction through adsorption and liquid phase surface tension enhancement. The findings in this work presents AAs as potential gas hydrate inhibitors for practical oil and gas industrial applications such as flow assurance and process facilities operations.